A lexical-cognitive approach to the influence of the media on the perceptions of Spanish university students regarding COVID-19 - Ávila Muñoz, Antonio Manuel; Santos Díaz, Inmaculada Clotilde; Ibáñez, Ester Trigo (Círculo de Lingüística Aplicada a la Comunicación, 2020)
The beginning of 2020 has been marked by the coronavirus crisis and its effects have been reported worldwide through different media. Considering that, especially at the beginning of the health emergency, the population was very aware of the media, this paper analyses how these have influenced the perception of reality directly associated with the pandemic and its consequences. The lexicon shared by a sample of Spanish university students has been studied using tools capable of opening a gateway to the community cognitive prototypes that arose as a result of this crisis of sanitary origin, although of economic and social scope. The results reflect hopeless collective conceptions that demonstrate "terror" in the face of the pandemic "strain" in the confinement situation, "uncertainty" in the future and the feeling of "lie" when it comes to politics. Furthermore, it is shown that increased exposure to the media further reinforces the general pessimistic view.